Holocaust Impiety in 21st Century Graphic Novels: Younger Generations ‘No Longer Obliged to Perpetuate Sorrow’ - Serraf, Lola (Genealogy (Basel), 2019)
At a time where so few survivors remain alive and the extermination of European Jews is leaving the field of direct human experience, the evolving collective memory of the event is reflected in popular culture. There has recently been a rise in the number of graphic novels written on the subject of the Shoah, particularly in France, Germany, and North America. These works, written by second or even third-generation survivors nearly 80 years after the genocide, approach the event from perspectives that not only further Art Spiegelman’s path in that they challenge the so-called limits of Holocaust representations, but also open up new discussions on transgenerational trauma. Focusing on two graphic novels, Michel Kichka’s Deuxième génération: Ce que je n’ai pas dit à mon père (2012) and Jérémie Dres’ Nous n’irons pas à Auschwitz (2011), my aim here is to examine the new aspects of trauma that these texts present, more specifically the reluctance to deal with one’s past, the struggle to bear the weight of the ‘sacred’ memory of Auschwitz, and in some cases the lack of interest of the youth in the Shoah. Both these autobiographical texts narrate the story of men who end up making the conscious decision never to go to Auschwitz after finding out about their ancestors’ history, asserting their desire to not solely be defined by their family tragedy. These issues, which fit in with what Matthew Boswell and Joost Krijnen define as ‘Holocaust impiety’, mark a break with graphic novels from the 1970s and 1980s which, as Gillian Rose writes, ‘mystified’ the event as ‘something we dare not understand’.